(untitled) - Deutsh, Babette (New York, 1957)
The classic reference work—an invaluable sourcebook for poets and readers
Keywords: English language,American poetry,English poetry,Poetry; Versification,Handbooks, manuals, etc,History and criticism,Handbooks, manuals, etc,History and criticism,Handbooks, manuals, etc,Authorship,Handbooks, manuals, etc